Agricultural clusters: a state of the art for field competitiveness studies - Tapia B., Lina; Aramendiz T., Hermes; Pacheco Q., Jessica; Montalvo P., Alba (Revista de Ciencias Agrícolas, 2015)
This article is a review of how the clustering phenomenon in agriculture has been studied, given the importance of the link between production and agricultural systems’management models for market equilibrium of food products, in an environment that promotes the accelerated growth of food production, industrial goods, and biofuels demand. For this, the relationship between agriculture, rural development, agrofood chains, and agricultural clusters is discussed. In addition, Latin American and international research that characterized, assessed, or designed agricultural clusters were selected in order to identify variables, approach types, study methods, and main contributions to improving their productivity and competitiveness. Overall, it was found that ad hoc case studies have been the most applied methods, followed by multivariate analysis and inputoutput tables. Further more, it was observed that the quantitative approach through mathematical simulation is just beginning to be included in the problem of designing agricultural clusters, and that concern for this topic in Latin America is also recent.